An Analysis of Grammatical Errors Made by the Teacher Professional Education Program Students in Giving Instructions - Ghina Seprifa; Witri Oktavia (Journal of English Language Teaching, 2021)
The purpose of this study was to find the grammatical errors made by Teacher Professional Education Program (PPG) Students in giving instructions at Universitas Negeri Padang. It employed descriptive research with PPG students 2021 majoring English as the population of the research. There were 33 PPG students taken as the sample of the research selected through total sampling technique. The data were collected through video recording when the Teacher Professional Education Program (PPG)  students teaching. The video recording was transcribed and analyzed when giving instructions. The result of the study showed the most type of errors made by Teacher Professional Education Program (PPG) students in giving instructions is addition error which consisted of 42 errors or 37% of errors.